2008
DOI: 10.1111/j.1460-9568.2008.06224.x
|View full text |Cite
|
Sign up to set email alerts
|

Dopamine modulates diurnal and circadian rhythms of protein phosphorylation in photoreceptor cells of mouse retina

Abstract: Many aspects of photoreceptor metabolism are regulated as diurnal or circadian rhythms. The nature of the signals that drive rhythms in mouse photoreceptors is unknown. Dopamine amacrine cells in mouse retina express core circadian clock genes, leading us to test the hypothesis that dopamine regulates rhythms of protein phosphorylation in photoreceptor cells. To this end we investigated the phosphorylation of phosducin, an abundant photoreceptor-specific phosphoprotein. In mice exposed to a daily light-dark cy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
63
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 70 publications
(64 citation statements)
references
References 52 publications
1
63
0
Order By: Relevance
“…Harvested retinas were immediately frozen on dry ice and stored at −80°C. The frozen retinas were processed using high-performance liquid chromatography (HPLC), as previously described (Nir et al, 2000; Pozdeyev et al, 2008). Right and left eyes of mice with a normal visual environment were pooled together for analysis, while eyes of FD mice were analyzed individually.…”
mentioning
confidence: 99%
“…Harvested retinas were immediately frozen on dry ice and stored at −80°C. The frozen retinas were processed using high-performance liquid chromatography (HPLC), as previously described (Nir et al, 2000; Pozdeyev et al, 2008). Right and left eyes of mice with a normal visual environment were pooled together for analysis, while eyes of FD mice were analyzed individually.…”
mentioning
confidence: 99%
“…Dopamine the reward-motivated neurotransmitter undergoes down regulation during stress condition in both light and dark exposures, revealing its direct association with sleep and stress. The observation also emphasizes its direct role in circadian cycle associated disturbances, as it was known that dopamine modulates diurnal and circadian rhythms in photoreceptor cells of mouse retina [11]. Serotonin, the other major neurotransmitter involved in cognitive functions was also found decreased in the disturbed cerebrum due to stress as it has been shown that serotonin has direct association with sleep as serotonin knockout mice exhibit more wakefulness [12].…”
Section: Discussionmentioning
confidence: 95%
“…For this reason, the relationship between severity of depression and CLOCK variants cannot be considered as a direct one. Nevertheless, for a better understanding of the possible influence of clock genes on depression, future studies should include other clock genes, haplotypes, and ideally the neurotransmitter systems that this molecular machinery are potentially influencing (Cuesta et al, 2008;Hampp et al, 2008;Imbesi et al, 2009;Pozdeyev et al, 2008;Yujnovsky et al, 2006).…”
Section: Discussionmentioning
confidence: 98%